2011
DOI: 10.3144/expresspolymlett.2011.44
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of microgel composite hydrogels by polymer post-crosslinking method

Abstract: Abstract.A novel post-crosslinking method by heating the composite polymer with dispersed reactive microgels was used to prepare microgel composite (MC) hydrogels. This MC hydrogels were crosslinked by reactive microgels instead of traditional crosslinkers. The reactive microgels contained hydroxymethyl groups, which acted as post-crosslinkers. They were prepared by inverse emulsion polymerization. The formed MC hydrogels at appropriate conditions had high equilibrium swelling ratio and excellent mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…So, another method was used to determine the crosslinking bond character. Hydrogen bonds can be determined simply by 0.1 M NaOH solution . As shown in Table , all natural drying MC polymers were soluble in 0.1 M NaOH solution.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…So, another method was used to determine the crosslinking bond character. Hydrogen bonds can be determined simply by 0.1 M NaOH solution . As shown in Table , all natural drying MC polymers were soluble in 0.1 M NaOH solution.…”
Section: Resultsmentioning
confidence: 99%
“…This natural drying polymer has soluble character, which can bring more convenience for studying the chemical reactions during the heating process. We have reported that the MC hydrogel was brittle and had low swelling ratio when the heating temperature was 90°C . So, the heating temperature range was chosen as 40°C–80°C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations